Effects of dietary inclusion of high concentrations of crude glycerin on meat quality and fatty acid profile of feedlot fed Nellore bulls - Van Cleef, Eric H. C. B. [UNESP]; D'Áurea, André P. [UNESP]; Fávaro, Vanessa R. [UNESP]; Van Cleef, Flavia O. S. [UNESP]; Barducci, Robson S. [UNESP]; Almeida, Marco T. C. [UNESP]; Machado Neto, Otávio R. [UNESP]; Ezequiel, Jane M. B. [UNESP] (Public Library of Science (PLoS), 2017)
Crude glycerin, the main by-product of biodiesel production, can replace dietary energy sources, such as corn. The objective of this study was to evaluate the inclusion of up to 30% of crude glycerin in dry matter (DM) of the total diets, and its effects on meat quality parameters of feedlot Nellore bulls. Thirty animals (227.7 ± 23.8 kg body weight; 18 months old) were housed in individual pens and fed 5 experimental diets, containing 0, 7.5, 15, 22.5 or 30% crude glycerin (DM basis). After 103 d (21 d adaptation) animals were slaughtered and the Longissimus muscle was collected. The characteristics assessed were chemical composition, fatty acid profile, cholesterol, shear force, pH, color, water-holding capacity, cooking loss and sensory properties. The increasing inclusion of crude glycerin in the diets did not affect the chemical composition of the Longissimus muscle (P > 0.10). A quadratic effect was observed when levels of crude glycerin were increased, on the concentration of pentadecanoic, palmitoleic and eicosenoic fatty acids in meat (P < 0.05), and on the activity of the delta-9 desaturase 16 and delta-9 desaturase 18 enzymes (P < 0.05). The addition of crude glycerin increased the gamma linolenic fatty acid concentration (P < 0.01), and altered the monounsaturated fatty acids in Longissimus muscle of animals (Pquad. < 0.05). Crude glycerin decreased cholesterol content in meat (P < 0.05), and promoted higher flavor score and greasy intensity perception of the meat (P < 0.01). The inclusion of up to 30% crude glycerin in Nellore cattle bulls'diets (DM basis) improves meat cholesterol and sensory attributes, such as flavor, without affecting significantly the physical traits, the main fatty acid concentrations and the chemical composition.